2015
DOI: 10.1159/000442441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D and Exercise on the Wellbeing of Older Community-Dwelling Women: A Randomized Controlled Trial

Abstract: Background: Evidence for the effects of exercise and vitamin D supplementation on quality of life (QoL), fear of falling (FoF) and mental wellbeing in older adults is conflicting. Objective: To study the effects of vitamin D supplementation and multimodal group exercise on psychosocial functions of wellbeing, including QoL, mental wellbeing and FoF. Method: This is a 2-year, double-blind, placebo-controlled vitamin D and open exercise intervention trial with 409 older Finnish women (70-80 years of age) randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…33 High-dose vitamin D did supplementation not improve quality of life as compared to standard dose. This is in accordance with other studies in elderly community-living participants 19,20 and in heart failure patients. 34 However, other studies have reported improvement in quality of life in patients with irritable bowel syndrome 17 as well as in patients with Crohn's disease, the latter in an uncontrolled trial.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…33 High-dose vitamin D did supplementation not improve quality of life as compared to standard dose. This is in accordance with other studies in elderly community-living participants 19,20 and in heart failure patients. 34 However, other studies have reported improvement in quality of life in patients with irritable bowel syndrome 17 as well as in patients with Crohn's disease, the latter in an uncontrolled trial.…”
Section: Discussionsupporting
confidence: 94%
“…This should be highly relevant in the context of the possible pleiotropic effects of vitamin D, where quality of life could be considered a composite end‐point integrating various health effects of vitamin D. Observational studies have reported positive associations between serum 25(OH)D levels and quality of life . The results from intervention studies are, however, conflicting …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, 409 home-dwelling 70-80-year-old women were randomly assigned to one of four groups: (a) vitamin D 20 µg/day (800 IU) and exercise(D + Ex + ) (b) placebo and exercise(D − Ex + ) (c) vitamin D 20 µg/day without exercise(D + Ex − ), and (d) placebo without exercise (D − Ex − ). The intervention results have been reported previously ( 13 , 22 ). Of the 370 women who completed the intervention, 15 were unable or unwilling to continue with the follow-up.…”
Section: Methodssupporting
confidence: 74%
“…Neither did another trial that investigated the effect of daily 800 IU vitamin D plus 1000 mg calcium vs placebo for 6 months among 2117 women age 70 years and older . And also a third trial testing daily dosing with 800 IU vitamin D (combined with and without exercise) came to the conclusion that vitamin D does not contribute to better mental well‐being in community‐dwelling women 70 years and older . Regarding larger bolus dosing of vitamin D, one large trial among 2258 women aged 70 years and older investigated the effect of an annual high dose of 500 000 IU vitamin D compared with placebo and equally did not find a significant difference in any measures of mental health scores across the study groups.…”
Section: Discussionmentioning
confidence: 99%